Phytochelatins: Advances in Tomato Research - Deyvid Novaes Marques; Salete Aparecida Gaziola; Fernando Angelo Piotto; Ricardo Antunes Azevedo (Agronomy)
Tomato (Solanum lycopersicum), which is considered one of the more important and widely cultivated crop members of the family Solanaceae, exhibits numerous biochemical mechanisms to alleviate the stress produced by various biotic and abiotic factors. Many researchers have found that phytochelatins (PCs) play an important role in these stress-alleviating mechanisms and, therefore, contribute significantly to the plant’s coping strategies, particularly under heavy metal exposure. Ongoing research has extensively investigated tomato genotypes in plant stress research, with a particular focus on heavy metal stress. The production of PCs, synthesized from glutathione, is regulated by various factors and different stressors. Here, we aim to provide an overview of the panorama regarding the synthesis of PCs in tomato under different environmental conditions and experimental settings, as well as provide information on their broader roles in biotechnology and modulating plant tolerance and responses across diverse stress conditions and treatments within the context of tomato research.